2016
DOI: 10.1681/asn.2016020237
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of Cytokine Signaling-1 Peptidomimetic Limits Progression of Diabetic Nephropathy

Abstract: Diabetes is the main cause of CKD and ESRD worldwide. Chronic activation of Janus kinase and signal transducer and activator of transcription (STAT) signaling contributes to diabetic nephropathy by inducing genes involved in leukocyte infiltration, cell proliferation, and extracellular matrix accumulation. This study examined whether a cell-permeable peptide mimicking the kinase-inhibitory region of suppressor of cytokine signaling-1 (SOCS1) regulatory protein protects against nephropathy by suppressing STAT-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 49 publications
5
40
0
Order By: Relevance
“…SOCS1-KIR was also shown to be atheroprotective in a type I diabetes mouse model, decreasing vascular plaque accumulation of lipids, macrophages, and T cells, and reducing aorta expression of pro-inflammatory cytokines and chemokines (Recio et al, 2014). More recently, this SOCS1-KIR peptide was demonstrated to further improve diabetes associated-renal damage in mice as well as reduce inflammation and fibrosis in diabetic kidneys (Recio et al, 2016). …”
Section: Socs1-derived Mimetic Peptidesmentioning
confidence: 99%
“…SOCS1-KIR was also shown to be atheroprotective in a type I diabetes mouse model, decreasing vascular plaque accumulation of lipids, macrophages, and T cells, and reducing aorta expression of pro-inflammatory cytokines and chemokines (Recio et al, 2014). More recently, this SOCS1-KIR peptide was demonstrated to further improve diabetes associated-renal damage in mice as well as reduce inflammation and fibrosis in diabetic kidneys (Recio et al, 2016). …”
Section: Socs1-derived Mimetic Peptidesmentioning
confidence: 99%
“…Because the relationship between oxidative stress and JAK2/STAT1 pathway is a common mechanism of diabetic tissue damage [20,21], this study aimed to establish the role of SOCS1, one of the most relevant SOCS family members, on redox regulation during development of diabetic complications. Previous animal studies from our group demonstrated that therapeutic targeting of SOCS family prevents tissue injury in both nondiabetic [23][24][25] and diabetic conditions [26][27][28]. Therefore, this work investigates the antioxidant effects of two different SOCS1-based strategies (adenovirus-mediated gene transfer and peptidomimetic of the kinase-inhibitory region) in the setting of diabetic micro-and macrovascular complications.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is one of the most prevalent causes of chronic kidney disease (CKD) [1] and end-stage-renal disease [2]. In the United States,~20-40% of DM patients develop diabetic nephropathy (DN) [3].…”
Section: Introductionmentioning
confidence: 99%